Corporate Communication Innovation: The Role of Mobile Technology and AI in Improving Public Connectivity - Irwansyah, Irwansyah; Megasari Panjaitan, Rina; Vielden Minanlarat, Kevin; Adityawan, Jonathan (Sahabat Publikasi, 2024)
This study aims to analyze the role of mobile technology and artificial intelligence (AI) in improving the effectiveness of corporate communication and corporate relationships with consumers. With the rapid development of digital technology, companies are required to adopt innovations that are able to answer consumer needs quickly and personally. The study examines the application of AI, such as chatbots and sentiment data analysis, as well as mobile technology as the main interaction platform. Data is collected through a literature study method that includes journals, articles, and recent case studies. The results show that AI contributes to brand responsiveness through fast, automated customer service and data-driven analysis of consumer needs. On the other hand, mobile technology provides flexibility for consumers to access services and interact with brands at any time. The combination of these two technologies creates a more personalized and relevant experience, but it also poses challenges such as data privacy protection and limitations in understanding consumers' emotional context. This study concludes that the integration of mobile technology and AI in corporate communication is an effective strategic step to improve public connectivity. However, successful implementation requires a balanced approach between automation and human interaction to build consumer trust on an ongoing basis